HABITUATING RELIGIOUS MODERATION IN ISLAMIC RELIGIOUS EDUCATION: STRATEGIES AND IMPLICATIONS FOR STUDENT TOLERANCE IN MULTICULTURAL SCHOOLS - Holis Andika; Achmad Mahrus Helmi; Suyono Suyono; Fahmi Ziyyad Al Afthoni (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
This study examines the habituation strategy of religious moderation in Islamic Religious Education (IRE) and its implications for fostering student tolerance in multicultural school settings. Employing a qualitative case study design, the research was conducted at SDN 2 Sukoreno Umbulsari, Jember. Data were collected through in-depth interviews, participant observation, and document analysis. The findings indicate that the habituation of wasathiyyah values is systematically implemented through the integration of IRE content with the hidden curriculum, particularly via diversity-oriented activities and role-playing practices. These strategies effectively cultivate key moderation principles, including tawasut (balance), tasamuh (tolerance), and I’tidal (justice). The study further reveals a notable enhancement in students’ tolerance and inclusive attitudes, as reflected in their capacity for respectful interfaith interaction and their ability to manage minor social conflicts constructively. The findings underscore the importance of institutional support through strengthened school policies and targeted professional development for IRE teachers focusing on habituation-based, multicultural pedagogical approaches. Ultimately, this study contributes to the discourse on religious moderation by demonstrating how schools can foster inclusive learning environments and prepare students to navigate complex social and global challenges.